Contestation of Legal and Social Norms in Early Marriage - Sopiyani, Sopiyani; Maksun, Maksun; Maskur, Ali (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This research discusses the phenomenon of early marriage that occurs in Pinayungan Village, Karawang Regency, by highlighting the imbalance between legal norms and social norms prevailing in the community. Although legal regulations, such as Law No. 16 of 2019 and PERMA No. 5 of 2019, have regulated the minimum age of marriage and marriage dispensation procedures for the protection of children's rights, the practice of early marriage is still rampant. Through a juridical-sociological approach and qualitative method, this study explores the sociocultural factors behind early marriage, including the belief in the